2021
DOI: 10.1093/plphys/kiab604
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin OsPIP2;2 links the H2O2 signal and a membrane-anchored transcription factor to promote plant defense

Abstract: To overcome pathogen infection, plants deploy a highly efficient innate immune system, which often uses hydrogen peroxide (H2O2), a versatile reactive oxygen species, to activate downstream defense responses. H2O2 is a potential substrate of aquaporins, the membrane channels that facilitate the transport of small compounds across plasma membranes or organelle membranes. To date, however, the functional relationship between aquaporins and H2O2 in plant immunity is largely undissected. Here, we report that the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 49 publications
1
33
0
Order By: Relevance
“…The function of ROS, including superoxide anion, H 2 O 2 , and hydroxyl radicals, in the plant resistance to pathogen mainly consists of direct antimicrobial ability, lignification of the cell wall, induction of HR, production of PR proteins, generation of phytoalexins (like flavonoid), and other defense responses ( Shetty et al., 2008 ; Li et al., 2021b ; Feng et al., 2022 ). H 2 O 2 , acting as a signal, can activate downstream defense responses, and recent studies showed that H 2 O 2 signal could be transduced to aquaporins to endow a resistant ability against pest ( Lu et al., 2022 ) and disease ( Zhang et al., 2021 ) in plant. In this paper, the content of superoxide anion was significantly higher in Tc3d than that in other treatments, while the content of H 2 O 2 was the lowest together with the C3d treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The function of ROS, including superoxide anion, H 2 O 2 , and hydroxyl radicals, in the plant resistance to pathogen mainly consists of direct antimicrobial ability, lignification of the cell wall, induction of HR, production of PR proteins, generation of phytoalexins (like flavonoid), and other defense responses ( Shetty et al., 2008 ; Li et al., 2021b ; Feng et al., 2022 ). H 2 O 2 , acting as a signal, can activate downstream defense responses, and recent studies showed that H 2 O 2 signal could be transduced to aquaporins to endow a resistant ability against pest ( Lu et al., 2022 ) and disease ( Zhang et al., 2021 ) in plant. In this paper, the content of superoxide anion was significantly higher in Tc3d than that in other treatments, while the content of H 2 O 2 was the lowest together with the C3d treatment.…”
Section: Discussionmentioning
confidence: 99%
“…7 ). Four aquaporins (PIP1–1, PIP2–1, and two isoforms of PIP2–2) involved in pathogen-induced H 2 O 2 transport [ 66 ] were also differentially regulated by Kac (Fig. 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…7 ). In addition, we found that four aquaporins involved in pathogen-induced H 2 O 2 transport [ 66 ] were also differentially regulated by Kac (Fig. 6 ) These findings suggest that Kac may response to pathogenic attack by regulating the activity of ROS scavenging-related proteins (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…AP2-ERF TFs were upregulated under low oxygen conditions in Arabidopsis , rice, and poplar ( Populus trichocarpa ) [ 30 , 31 ] and shown to regulate genes encoding respiratory enzymes and ROS scavengers [ 32 ]. In addition, some of the TFs may be involved in regulation of aquaporin expression, including MYB [ 33 ] and ERF [ 34 ]. Translucent green, which belongs to the ERF family, was reported to directly regulate the expression of AtTIP1 ; 1 , AtTIP2 ; 3 , and AtPIP2 ; 2 in Arabidopsis [ 34 ], and OsPIP2 ; 2 in Oryza sativa triggers translocation of OsmaMYB TF [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some of the TFs may be involved in regulation of aquaporin expression, including MYB [ 33 ] and ERF [ 34 ]. Translucent green, which belongs to the ERF family, was reported to directly regulate the expression of AtTIP1 ; 1 , AtTIP2 ; 3 , and AtPIP2 ; 2 in Arabidopsis [ 34 ], and OsPIP2 ; 2 in Oryza sativa triggers translocation of OsmaMYB TF [ 33 ].…”
Section: Introductionmentioning
confidence: 99%